DIVERSIFIKASI PRODUK PERUSAHAAN AIR MINUM DESA BUMDES MAKMUR ANUGERAH LESTARI KECAMATAN CIOMAS, BOGOR – JAWA BARAT - irmawaty, irmawaty; Khurniawan, Arie Wibowo; Sunarsih, Nenah; Nasoha, Muhammad; Surapto, Deni (Gandhi: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity was conducted to assist BUMDes Makmur Anugerah Lestari, Ciomas, Bogor in product diversification. BUMDes Makmur Anugerah Lestari operates several business units, including Reverse Osmosis (RO) refillable water and village PAM (Public Water Supply) systems. Recognizing the availability of several exploitable water sources and the significant community demand for drinking water, a product diversification initiative was undertaken. The objective of this program was to diversify into packaged drinking water products. The methodology employed in this community service (PkM) program involved training and water potability testing. The training focused on labelling and packaging. The results of the water potability tests indicated that the microbiological parameters for E. coli were 0 and the total coliform bacteria were 0, signifying good water quality suitable for consumption. Two packaging sizes were developed for bottling. This activity significantly impacted the diversification of drinking water products through the conducted potability tests, confirming that the water sourced for the packaged drinking water products is of good quality and safe for consumption. The PkM team diversified into 600 ML and 300 ML bottled drinking water. Based on the training outcomes, Mitra (partner) is now capable of creating appealing labels and packaging for bottled water products. Through this PkM activity, the community is empowered to be more creative and independent, contributing to the advancement of the village.